Implementation of CMM Method to Measure Maturity Level of SPBE in Palembang City Government - Nyimas Hamidah Purnama Agustriani; Marsudi Wahyu Kisworo; Edi Surya Negara; Usman Ependi (Sinkron : jurnal dan penelitian teknik informatika, 2026)
The Palembang City Government faces challenges in synchronizing internal policies with the operational implementation of the Electronic-Based Government System (SPBE). This research aims to measure the maturity level of the Internal Policy Domain and the SPBE Governance Domain in the Palembang City Government using the Capability Maturity Model (CMM) method. Additionally, the study aims to identify gaps through gap analysis and formulate strategic recommendations to achieve the "Optimum" maturity level. The research focuses on evaluating 20 indicators covering the Internal Policy and SPBE Governance domains within the Palembang City Government. The maturity level analysis refers to the framework of Permenpan-RB No. 59 of 2020 and Menpan-RB Guideline No. 3 of 2024. The indicator assessment results show that the Internal Policy Domain reached an index of 4.1 (Very Good), while the Governance Domain obtained an index of 3.4 (Good). Overall, the Palembang City Government possesses a very strong regulatory foundation; however, governance effectiveness remains sectoral and is not yet fully aligned with technical implementation across all regional apparatus. It is recommended that the Palembang City Government strengthen cross-sector coordination through integrated SPBE budget synchronization and conduct periodic policy reviews accompanied by formal documentation to ensure the sustainable improvement of SPBE quality.